2002
DOI: 10.1055/s-2002-33089
|View full text |Cite
|
Sign up to set email alerts
|

Meconium Stimulates Neutrophil Oxidative Burst

Abstract: Acute lung injury induced by meconium aspiration is characterized by rapidly developing pulmonary inflammation with influx of activated polymorphonuclear cells. To evaluate the role of meconium in the activation of these invading cells, we described the oxidative capacity of circulating neutrophils after intratracheal administration of thick human meconium in pigs. We also examined the direct effects of varying meconium concentrations on the oxidative burst of human neutrophils in vitro. In neutrophils isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…Superoxide also increases the relaxation of musculature by entering into reaction with oxygen and by reducing bioavailability of the nitric oxide. Role of the oxygen in changing of the reaction of the smooth musculature of pulmonary artery is related with the syndrome of aspiration of the meconial fluid; this is also reported by other authors [27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 63%
“…Superoxide also increases the relaxation of musculature by entering into reaction with oxygen and by reducing bioavailability of the nitric oxide. Role of the oxygen in changing of the reaction of the smooth musculature of pulmonary artery is related with the syndrome of aspiration of the meconial fluid; this is also reported by other authors [27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 63%
“…4,8,10,18 Ex vivo studies using a piglet model show that moderate and high concentrations of aspirated meconium rapidly activate circulating neutrophils. 19 Experimental study in piglet model suggests that meconium-induced inflammation is localized in the meconium-contaminated areas of the lungs with no generalized inflammatory injury. 20 Correspondingly, local accumulation of neutrophils and macrophages and production of IL-1b and tumor-necrosis factor-a (TNFa) cytokines have been observed.…”
Section: Neutrophil Influxmentioning
confidence: 99%
“…29 Neutrophil influx following meconium exposure may also activate alveolar macrophages to produce oxygen radicals, which may, at least in part, explain the proapoptotic effect of meconium in animal and human lungs. 17,19 Nitric oxide and apoptosis Although the bulk of evidence indicates that nitric oxide (NO) may induce apoptosis in different cell lines, including macrophages, it may have a dual effect. It is interesting to note that inhaled smaller quantities of NO may also inhibit apoptosis.…”
Section: Oxygen Radicals In Apoptosismentioning
confidence: 99%
“…30 Recently, it has been showed that meconium has an inhibitory effect on neutrophils in low concentrations (0.2 mg ml À1 ) but in higher concentrations (1 and 2 mg ml À1 ) stimulates neutrophil oxygen radical production progressively. 31 A possible role for complement in meconium-induced oxidative burst has been recently postulated (see below).…”
Section: Inflammatory Mediators In Masmentioning
confidence: 99%